MENYELISIK POLA KEKERABATAN BAHASA MELALUI CERITA RAKYAT BERJUDUL I KEDIS CANGAK (PEDANDA BAKA) DI BALI: ANALISIS LINGUISTIK HISTORIS KOMPARATIF - Muhammad Aditya Wisnu Wardana; M. Furqon Al Maarif; Zanida Zulfana Kusnasari; Slamet Mulyono (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2023)
The diversity of languages in Indonesia is one of the advantages possessed by Indonesia as a multicultural and multilingual nation. The variety of languages speakers use is not the same; changes occur in various languages because speakers of a language usually make contact or relationships with speakers of other languages and occur over a long period. The comparative method is one of the methods used to compare languages in detail and systematically to prove historical or historical relationships between these languages. Comparative studies are always related to lexicostatistical calculations called internal reconstructions. This research is classified as descriptive research. In this study, the data were explained to obtain an adequate description of the research object without any manipulation or treatment of the subject and research object. The subject of this research is Balinese folklore with the title I Kedis Cangak (Pedanda Baka), which can be found on the page https://www.komangputra.com/av/kedis-cangak The technique used in this study is note-taking, in which the author carefully reads the folklore I Kedis Cangak (Pedanda Baka) and then notes every word that has something in common with Indonesian. The results of this study were the number of syllables, sound patterns, affixes, and basic word patterns in the folklore I Kedis Cangak (Pedanda Baka). The results of this study are the similarities and differences between BB and BI at the phonological level. These similarities and differences relate to the type and number of phonemes, diphthongs, clusters, and syllable patterns in BB and BI.